MANAGING THYROTOXIC ATRIAL FIBRILLATION IN A BIOCHEMICALLY EUTHYROID PATIENT - I, Hazwani; Chuan, Ng Ooi; RMR, Raja Abdul Wafy (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyperthyroidism induces cardiovascular changes like increased heart rate and atrial automaticity, leading to conditions such as atrial fibrillation and heart failure, contributing to higher mortality rates. Despite achieving euthyroidism with treatment, cardiovascular manifestations may persist, necessitating further investigation into factors associated with persistent atrial fibrillation to guide appropriate anticoagulation therapy. CASE 1 A 66-year-old Malay male with high blood pressure, dyslipidaemia, and thyrotoxic atrial fibrillation (TAF) due to Graves’ disease of 5 years duration. He had two failed radioactive iodine treatments and thyroid surgery. He had periodic palpitations, dyspnoea, and left chest pain. His ECG revealed rapid atrial fibrillation. He has uncontrolled elevated blood pressure. The thyroid function tests were normal (T4 = 14.21, TSH = 4.78). He was eventually referred to the cardiology team who recommended cardiac ablation. CASE 2 A 34-year-old female with Graves’ disease and atrial fibrillation (AF) despite taking bisoprolol, went to the emergency department due to frequent palpitations and dizziness. She did not have chest pain. Her ECG showed atrial fibrillation. She had normal thyroid function tests (T4 = 15.21, TSH = 3.56) with elevated troponin levels. She was treated for symptomatic AF. She was subsequently referred to cardiology for cardiac ablation. CONCLUSION Thyroid hormones affect cardiovascular function, predisposing hyperthyroid individuals to atrial fibrillation even after achieving euthyroidism. The thromboembolic risk in TAF is reduced by oral anticoagulants. Treatment for TAF involves antithyroid medications to restore euthyroidism together with rate and rhythm regulation. Wong et al., found an unexpected relationship between decreased free thyroxine levels and chronic atrial fibrillation. TAF has a high thromboembolic risk even after euthyroidism, requiring anticoagulants and ongoing monitoring to prevent recurrence. Sometimes ablation is recommended, especially for persistent AF. In conclusion, hyperthyroidism-related AF therapy requires collaboration between endocrine and cardiovascular specialists. Prompt diagnosis and personalised treatment can improve the prognosis and reduce complications.